Election administration in crisis: an early look at lessons from Bush versus Gore - Wise, Charles R. (2001)
The 2000 presidential election exposed serious election-administration deficiencies that affected the presidential election and the confidence of the American people in the way elections are administered. The ensuing controversies also exposed significant issues in judicial-administrative relations. This article examines the factors involved not only in Florida, but also in the nation, and discusses lessons for the future of election administration and for public administration generally. - Reproduced
Keywords: Presidents - United States - Elections; Elections - United States; Elections